Retinal Thickness Analysis in Progressive Multiple Sclerosis Patients Treated With Epigallocatechin Gallate: Optical Coherence Tomography Results From the SUPREMES Study - Klumbies, Katharina; Rust, Rebekka; Dörr, Jan; Konietschke, Frank; Paul, Friedemann; Bellmann-Strobl, Judith; Brandt, Alexander U.; Zimmermann, Hanna G. (Frontiers in Neurology, 2021)
Background: Epigallocatechin gallate (EGCG) is an anti-inflammatory agent and has proven neuroprotective properties in animal models of multiple sclerosis (MS). Optical coherence tomography (OCT) assessed retinal thickness analysis can reflect treatment responses in MS. Objective: To analyze the influence of EGCG treatment on retinal thickness analysis as secondary and exploratory outcomes of the randomized controlled Sunphenon in Progressive Forms of MS trial (SUPREMES, NCT00799890). Methods: SUPREMES patients underwent OCT with the Heidelberg Spectralis device at a subset of visits. We determined peripapillary retinal nerve fiber layer (pRNFL) thickness from a 12° ring scan around the optic nerve head and thickness of the ganglion cell/inner plexiform layer (GCIP) and inner nuclear layer (INL) within a 6 mm diameter grid centered on the fovea from a macular volume scan. Longitudinal OCT data were available for exploratory analysis from 31 SUPREMES participants (12/19 primary/secondary progressive MS (PPMS/SPMS); mean age 51 ± 7 years; 12 female; mean time since disease onset 16 ± 11 years). We tested the null hypothesis of no treatment*time interaction using nonparametric analysis of longitudinal data in factorial experiments. Results: After 2 years, there were no significant differences in longitudinal retinal thickness changes between EGCG treated and placebo arms in any OCT parameter (Mean change [confidence interval] ECGC vs. Placebo: pRNFL: −0.83 [1.29] μm vs. −0.64 [1.56] μm, p = 0.156; GCIP: −0.67 [0.67] μm vs. −0.14 [0.47] μm, p = 0.476; INL: −0.06 [0.58] μm vs. 0.22 [0.41] μm, p = 0.455). Conclusion: Retinal thickness analysis did not reveal a neuroprotective effect of EGCG. While this is in line with the results of the main SUPREMES trial, our study was probably underpowered to detect an effect. Clinical Trial Registration:www.ClinicalTrials.gov, identifier: NCT00799890.